“I’m the only one that knows what I can and can’t do.”: Shaping identities through disability accommodation discussions - Milburn, Lindsey H. (Kansas State University, 2019)
This research project sought to understand experiences people with disabilities have when disclosing disability in the workplace for accommodations and how those experiences influenced identity formation. Utilizing a feminist disability theory framework, this project involved using semi-structured interviews with 13 people with cognitive and physical disabilities to learn more about their experiences across several organizational fields. Analysis of these interviews pointed to barriers within the workplace when navigating accommodation discussions based on relationships with others, degree of disability support in the organization, and understanding of disability experiences and accommodation needs. When accommodations are genuinely fulfilled, employees with disabilities feel supported and empowered; when they are not fulfilled, employees with disabilities feel excluded, vulnerable, and like an inconvenience. This research sheds light onto some experiences with disabilities and provides meaningful suggestions for organization leaders seeking an inclusive and welcoming environment for people with disabilities.
Keywords: People with disabilities; Workplace accommodations; Disability; Identity; Empowerment; Accommodation